PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PERUSAHAAN (Studi pada Perusahaan Food and Beverages yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2012-2016) - Retna Iswandari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to determining the effect of working capital on the company’s profitability. The independent variables are inventory conversion period, average collection period, payable defferal period and cash conversion cycle. The dependent variable of this is profitability measured using Return on Asset (ROA).This quantitative research is an explanatory research which explains the relation or influence among variables. From a population of 14 food and beverages and used non- probability sampling method with a sampling technique using purposive sampling. This studu uses secondary data in a form annual financial report of food and beverages companies dusring 2012-2016, which were obtained from the Indonesia Stock Exchange and were then analyzed using Multiple Linear Regression.The partical test of the research shows that average collection period, payable defferal period and cash conversion cyle has a negative and significant relation with probability and inventory conversion period have a positive and significant relation with probability (ROA).Keywords : Profitability, Cash Conversion Cycle, Inventory Conversion Period, Average Collection Period and Payable Defferal Period